Isolation, identification, and antibacterial evaluation of endophytic fungi from Gannan navel orange - Wang, Huan; Liu, Ziyue; Duan, Fangfang; Chen, Yan; Qiu, Kaidi; Xiong, Qin; Lin, Huiting; Zhang, Jun; Tan, Haibo (Frontiers in Microbiology, 2023)
Gannan navel orange is a famous brand in China but the isolation of its endophytic fungi was rarely reported. In this study, a total of 54 strains of endophytic fungi were successfully isolated from the pulp, peel, twig, and leaf of Gannan navel orange; they were successfully identified to belong to 17 species of 12 genera. All these strains were fermented using potato-dextrose agar (PDA) medium, and their secondary metabolites were then extracted with ethyl acetate (EtOAc). The antibacterial assays of Escherichia coli (E. coli), methicillin-resistant Staphylococcus aureus (MRSA), and Xanthomonas citri subsp. citri (Xcc) were also performed for the EtOAc extracts of these strains. As a result, the extracts of both Geotrichum sp. (gc-1-127-30) and Diaporthe biconispora (gc-1-128-79) demonstrated significant antibacterial activities against Xcc, and the MIC value for the extract of Colletotrichum gloeosporioides against MRSA was low to 62.5 μg/mL. Moreover, the chemical components of the extracts of Colletotrichum sp., Diaporthe biconispora, and Annulohypoxylon atroroseum were primarily investigated, and they successfully led to the isolation of 24 compounds involving a new botryane sesquiterpene. Among the isolated products, compound 2 showed significant inhibitory activities toward SA, MRSA, E. coli, and Xcc with MIC values of 12.5, 3.1, 125, and 12.5 μg/mL, respectively. This study revealed that the endophytic fungi of Gannan navel orange showed high potency to produce secondary metabolites with significant antibacterial effects.